Geology and geochemistry of Zn-Pb(-Ge-Ag) deposits in the Sichuan-Yunnan-Guizhou Triangle area, China: A review and a new type - Runsheng, Han; Yan, Zhang; Wenlong, Qiu; Tianzhu, Ding; Mingzhi, Wang; Feng, Wang (Frontiers in Earth Science, 2023)
Mississippi Valley Type (MVT) deposits represent the majority of carbonate-hosted Zn–Pb deposits globally. They typically form in an extensional tectonic setting along passive basin margins. However, studies on carbonate-hosted Zn–Pb deposits in the Sichuan–Yunnan–Guizhou Triangle area (SYGT) reveal differences in terms of the essential features of typical MVT deposits. We discuss the main features of these deposits, characterised by fault-fold structural controls, high-grade Zn–Pb ores and symbiotic or associated elements (i.e., abundant Ag and dispersed amounts of Ge, Ga, and Cd) of significant economic value. Based on a comparison of Pb-Zn deposits in SYGT and classical MVT deposits formed in an extensional tectonic setting, as well as a subsequent discussion on deposit classification, we propose that the Huize-style Zn–Pb deposits are a new deposit style, whose basic features can guide future ore exploration. We define the Huize-style deposits based on four factors: (i) Hierarchical ore-controlling system of strike-slip fault-fold structures; (ii) litho-facies associated with typical alternation and mineralisation; (iii) ore-forming geochemical features revealed by typical mineral assemblages, mineralisation alteration zoning, fluid-inclusion, isotope geochemistry and metallogenic acid–alkali geochemical barriers; and (iv) different prospecting methods to those typically used for MVT deposits. The Huize-style and typical MVT deposits constitute the carbonate-hosted non-magmatic epigenetic hydrothermal-type (CNHT) Zn–Pb deposits.